The discovery of Foxl2 paralogs in chondrichthyan, coelacanth and tetrapod genomes reveals an ancient duplication in vertebrates - Geraldo, M. T. [UNESP]; Valente, G. T. [UNESP]; Braz, A. S K; Martins, C. [UNESP] (Springer Nature, 2013)
The Foxl2 (forkhead box L2) gene is an important member of the forkhead domain family, primarily responsible for the development of ovaries during female sex differentiation. The evolutionary studies conducted previously considered the presence of paralog Foxl2 copies only in teleosts. However, to search for possible paralog copies in other groups of vertebrates and ensure that all predicted copies were homolog to the Foxl2 gene, a broad evolutionary analysis was performed, based on the forkhead domain family. A total of 2464 sequences for the forkhead domain were recovered, and subsequently, 64 representative sequences for Foxl2 were used in the evolutionary analysis of this gene. The most important contribution of this study was the discovery of a new subgroup of Foxl2 copies (ortholog to Foxl2B) present in the chondrichthyan Callorhinchus milii, in the coelacanth Latimeria chalumnae, in the avian Taeniopygia guttata and in the marsupial Monodelphis domestica. This new scenario indicates a gene duplication event in an ancestor of gnathostomes. Furthermore, based on the analysis of the syntenic regions of both Foxl2 copies, the duplication event was not exclusive to Foxl2. Moreover, the duplicated copy distribution was shown to be complex across vertebrates, especially in tetrapods, and the results strongly support a loss of this copy in eutherian species. Finally, the scenario observed in this study suggests an update for Foxl2 gene nomenclature, extending the actual suggested teleost naming of Foxl2A and Foxl2B to all vertebrate sequences and contributing to the establishment of a new evolutionary context for the Foxl2 gene. © 2013 Macmillan Publishers Limited All rights reserved.
Keywords: Forkhead box L2; Gene duplication; Paralog copies; Vertebrate genome; gene expression; genome; homology; nomenclature; phylogeny; polyploidy; teleost; Aves; Callorhinchus milii; Coelacanthidae; Didelphidae; Eutheria; Latimeria; Latimeria chalumnae; Metatheria; Monodelphis domestica; Taeniopygia guttata; Teleostei; Tetrapoda; Vertebrata